English education in Oman current scenarios and future trajectories - Mahrooqi, Rahma al-; Denman, Christopher (Springer, 2018)
This book explores an area that has been somewhat overlooked in the literature to date - the current status and future trends of English education in Oman. It offers a variety of theoretical and methodological approaches to the subject and explores areas of English education in Oman that have, until now, been little investigated. It explores these issues from a variety of perspectives: the professionalization of English teachers in the country; the implementation of novel teaching methodologies, curricula, and assessment approaches, into what are, in many ways, still very traditional education settings; the integration of learner identity into English language instruction; country- and culture-specific concerns with conducting research with Omani participants; the strategic demands of building stronger links between education and workforce needs; and developing learner autonomy and motivation
Keywords: Language Education; Teaching and Teacher Education; Learning & Instruction; Education; Language and education; Teaching; Englischunterricht; Oman; Aufsatzsammlung